Prepectoral Breast Reconstruction with Polyurethane-Coated Implants: A 117-Patient Single-Center Study with Objective Cosmetic Evaluation - Kurt, Sevgi; Demir, Isil Akgun; Celik, Naci; Yazar, Memet; Ozkurt, Enver; Koc, Ertan; Ozmen, Vahit (Springer, 2026)
Background Prepectoral breast reconstruction with polyurethane (PU)-coated implants has been proposed to enhance implant stability and reduce complications. Evidence regarding their clinical and aesthetic performance remains limited. Methods A retrospective review was performed on 117 patients (186 breasts) who underwent immediate prepectoral reconstruction with PU-coated implants between 2020 and 2025. Complications were analyzed with univariate and multivariable regression. Aesthetic outcomes were evaluated using BCCT.core software. Results At a median follow-up of 15 months, 34 patients (29.1%) experienced at least one complication, most commonly rippling or upper-pole visibility (16.2%). Implant loss occurred in 3.4% and capsular contracture in 1.7%. Higher BMI, larger implant size, and skin-reducing mastectomy were associated with increased complication risk, although none remained independently significant. Chemotherapy had no measurable impact, and radiotherapy showed only a mild trend toward poorer aesthetic scores. Overall, 81.2% of patients achieved excellent or good BCCT.core results. Younger age and absence of complications were the strongest predictors of favorable aesthetic outcomes. Conclusions PU-coated implants provided stable outcomes in prepectoral reconstruction, with low implant loss and rare contracture. Most patients achieved favorable cosmetic results without the need for additional reinforcement materials. Higher BMI, larger implants, smoking, and skin-reducing mastectomy increased complication risk primarily in univariate analyses. Prospective multicenter studies with longer follow-up and patient-reported outcomes are required to validate these findings.
Keywords: Prepectoral breast reconstruction; Polyurethane-coated implants; Microthane implants; BCCT.core; Aesthetic outcomes; Complications